Estimating internal quantum efficiency of light-emitting diodes from current–voltage curves. (5th February 2019) - Mi, Chenziyi; Wang, Lai; Jin, Jie; Hao, Zhibiao; Luo, Yi; Sun, Changzheng; Han, Yanjun; Xiong, Bing; Wang, Jian; Li, Hongtao
Abstract: This work presents an approach to estimate the internal quantum efficiency (IQE) of commercial visible light-emitting diodes (LEDs) with the I–V characteristics. A narrow range of I–V curve, where the ideality factor is minimum, is chosen to be fitted by a parallel model of different current components. Then the IQE in this current range is calculated as the proportion of radiative recombination current and used as a reference to deduce the IQE from the external quantum efficiency. With this method, it founds that the peak IQE of blue and red LEDs exceeds 90% while that of green ones exceeds 60%.